2022
DOI: 10.1111/csp2.12663
|View full text |Cite
|
Sign up to set email alerts
|

Principles for the production of evidence‐based guidance for conservation actions

Abstract: Many types of guidance documents inform conservation by providing practical recommendations for the management of species and habitats. To ensure effective decisions are made, such guidance should be based upon relevant and up‐to‐date evidence. We reviewed conservation guidance for mitigation and management of species and habitats in the United Kingdom and Ireland, identifying 301 examples produced by over 50 organizations. Of these, only 29% provided a reference list, of which only 32% provided reference(s) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Actions taken by business are often informed by guidance documents, consultants (many of which rely on guidance themselves) or adherence to standards, certifications, principles or policy (White et al in review). However, reviews of guidance documents for management and mitigation in the UK and Ireland have identified poor use of scientific evidence to support recommendations: many documents commonly used for development projects are out-of-date, based on circular referencing of other guidance publications, and show limited use of primary empirical literature to support claims (Hunter et al 2021;Downey et al 2022). These results are of particular concern given Europe's comparatively strong research and information base, regulations and exceptional biodiversity monitoring, combined with relatively low species diversity compared to many other regions, which should mean that evidence can be more easily put into practice in development projects (Moussy et al 2022).…”
Section: The Benefits and Status Of Evidence-based Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…Actions taken by business are often informed by guidance documents, consultants (many of which rely on guidance themselves) or adherence to standards, certifications, principles or policy (White et al in review). However, reviews of guidance documents for management and mitigation in the UK and Ireland have identified poor use of scientific evidence to support recommendations: many documents commonly used for development projects are out-of-date, based on circular referencing of other guidance publications, and show limited use of primary empirical literature to support claims (Hunter et al 2021;Downey et al 2022). These results are of particular concern given Europe's comparatively strong research and information base, regulations and exceptional biodiversity monitoring, combined with relatively low species diversity compared to many other regions, which should mean that evidence can be more easily put into practice in development projects (Moussy et al 2022).…”
Section: The Benefits and Status Of Evidence-based Actionmentioning
confidence: 99%
“…A review of guidance documents in the UK and Ireland identified that only 9% of documents provided a reference to justify the actions that were recommended (Downey et al, 2022). For the UK housing sector, 56% of mitigation actions were justified by citing guidance documents, but <10% of the cited texts within these guidance documents looked at evidence of effectiveness.…”
Section: Issue Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Guidance documents vary in terms of scope and structure but can be defined as “an authoritative source of information and recommendations with the objective of informing… decisions and actions” (Downey et al, 2022). Concise, accessible and robust guidance can increase the use of empirical evidence in decision‐making, and guidance documents can, and should, be a key part of the conservation decision‐making landscape (Turner et al, 2019; Walsh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Concise, accessible and robust guidance can increase the use of empirical evidence in decision‐making, and guidance documents can, and should, be a key part of the conservation decision‐making landscape (Turner et al, 2019; Walsh et al, 2019). Guidance can also provide a critical overview of the available evidence and knowledge gaps, sometimes highlighting context‐specific implementation issues and uncertainties (Downey et al, 2022). The level of detail, context, and scale of guidance can be very flexible and depends greatly on its intended use.…”
Section: Introductionmentioning
confidence: 99%